Efektivitas Pemanfaatan Instagram dalam Meningkatkan Penjualan Produk Batik di Kota Surakarta - Dimas Muhammad Tri Nugroho (Study of Applied Entrepreneurship, 2024)
This study aims to analyze the effectiveness of using Instagram as a promotional medium and formulate an effective strategy for batik UMKM in Surakarta City in increasing sales. This study uses a qualitative descriptive approach with the object of research being batik UMKM in Surakarta City that use Instagram as a promotional medium, have a minimum of 1000 followers, and have been selling online for at least 1 year. Data were collected through observation, interviews, literature studies, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Instagram is an effective promotional medium for increasing sales of batik products. The right strategy for using Instagram can increase the number of followers, engagement, brand awareness, and ultimately increase sales. The effectiveness of the strategy for using Instagram is influenced by several factors, including product quality, price, brand image, competitors, and market trends. (Contains problems that occur so that research is conducted on the problem)